2014
DOI: 10.1108/prog-01-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management reliability and its impact on organizational performance

Abstract: Purpose – Although the topic of knowledge management (KM) failure has emerged over the past several years, no specific theory has been proposed about the ability of an organization to discover and manage unexpected failures in the organizational capabilities of KM. Thus, the main aim of this paper is to develop a theory of KM reliability by taking into account the availability of existing theory of high reliability for organizations. Furthermore, this study aims to empirically evaluate the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…It was found that the overall performance of organizations is linked with the knowledge. Using a sample of 245 organizations based in North American region, it was found by (Mahdavi Mazdeh & Hesamamiri ,2014) that the measures of performance a significantly influenced by KM. These measures include internal, financial and processes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the overall performance of organizations is linked with the knowledge. Using a sample of 245 organizations based in North American region, it was found by (Mahdavi Mazdeh & Hesamamiri ,2014) that the measures of performance a significantly influenced by KM. These measures include internal, financial and processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternatively, the relation between performance and KM has been analysed in literature. The focus is on the determination of performance in terms of competitiveness, effectiveness, and market performance and balanced scorecard (Mahdavi Mazdeh & Hesamamiri, 2014;Soto-Acosta, Popa, & Palacios-Marqués, 2016). There is limited number of studies on analysing the influence of KM on operational performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KM has been growing in importance and popularity as a research topic since the mid-1990s. It is defined as the process of selectively applying knowledge from previous experiences of decision-making to current and future decision-making activities with the express purpose of improving the organization's effectiveness (Mahdavi Mazdeh and Hesamamiri, 2014). According to this definition, KM involves identifying critical knowledge, acquiring critical knowledge in a knowledge base or organizational memory, sharing the stored knowledge, applying knowledge to appropriate situations, determining the effectiveness of using the applied knowledge and adjusting the knowledge use to improve the effectiveness of the organization (Jennex and Olfman, 2004;Alavi and Leidner, 2001).…”
Section: Literature Review 21 Strategy For Kmmentioning
confidence: 99%
“…Performance assessment and organizational rankings have attracted the attention of many researchers in the past few decades. Several performance assessment tools have been developed to assess organizational performances and analyze their rankings (Moore, 2007; Puri and Yadav, 2013, 2014; Mahdavi and Hesamamiri, 2014; Abbasi and Kaviani, 2016; Lv and Ma, 2019; Chen et al , 2020b). Data envelopment analysis (DEA), developed by Charnes et al (1978), is one among these performance tools.…”
Section: Introductionmentioning
confidence: 99%